Effect of dispersant types on the rheological and mechanical properties of oil well cement paste with nanosilica. (15th February 2021) - Xu, Yang; Liu, Ming; Li, Pengpeng; Zhu, Li; Xia, Xiujian; Zhang, Chi; Yu, Yongjin; Guo, Jintang
Highlights: Properties of cement paste containing NS with three dispersants are investigated. Working mechanisms of cement paste with AFS, PC and APC dispersants are discussed. APC shows better rheological and mechanical properties than AFS and PC. Abstract: This work evaluated the effect of various types of dispersants on rheological and mechanical properties of nanosilica filled cementitious composites. Three oil well cement dispersants, acetone formaldehyde sulfite (AFS), polycarboxylate (PC) and amphoteric polycarboxylate (APC) with various dosages (0.5%, 1.0% and 1.5% by weight of cement) were utilized to investigate the performance and working mechanism of dispersant in cementitious composites containing nanosilica. Results show that nanosilica adversely affects the rheological properties of cementitious materials, while PC and APC dispersants improve the rheological performance in comparison to AFS dispersant. Besides, cement hydration and microstructure for cement with various dispersants were characterized by Isothermal Calorimeter, X-ray Diffractometer, Thermal Gravimetry and Scanning Electron Microscopy. The PC dispersant with numerous carboxyl groups exhibits retardation of cement hydration, which shows a negative impact on the development of early compressive strength of set cement. The introduction of cationic groups in APC dispersant enhances its dispersion ability and alleviates the retardation from carboxylic groups in PC dispersants, which ensures better dispersion of nanosilica and cement particles and hence better mechanical properties. And all dispersants improve the compactness and microstructure of set cement due to uniform dispersion of nanosilica in cement, and hence advance the development of mechanical properties of nanosilica filled cementitious composites.